Hubungan Derajat Keparahan Akne Vulgaris dengan Kualitas Hidup menggunakan Dermatology Life Quality Index (DLQI) - Sachio, Alvin; Vera Madonna Lumban Toruan; Yuniati (Jurnal Kebidanan Mutiara Mahakam, 2020)
Background: Quality of life is an individual's perception of his life in the context of culture and values ​​in a place of residence with the relationship of goals, expectations, standards and concerns. Acne is a problem that can have an impact on a person's quality of life because of the shame felt by sufferers. Purpose : To describe the relationship between severity degree of acne vulgaris with quality of life using the Dermatology Life Quality Index assessment. Methods : This research is an analytical observational research with cross sectional method and the sampling was chosen by purposive sampling. The sample size of this study was 60 respondents, assessing quality of life using the DLQI questionnaire instrument. Result : Statistical test data indicate that there is no relationship between the severity degree of acne vulgaris with quality of life (p = 0,101). Conclusion : There is no correlation between the severity of acne vulgaris with quality of life using the Dermatology Life Quality Index (DLQI) assessment.